Neurovascular relationships in uterine wall in adenomyosis complicated with pelvic pain syndrome. - Orazov, M.; Sulaeva, O. N.; Nosenko, E. N. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Pelvic pain is one of the most frequent complications of adenomiosis. Objective. To investigate the neurovascular relationships in uterine adenomyosis complicated with pelvic pain syndrome. Methods. Material was received after hysterectomy from 16 patients of reproductive age with diffuse adenomyosis of 2-3 degrees in the phase of proliferation. The group of comparison included the material obtained from patients with asymptomatic leiomyoma. Morphological and immunohistochemical methods were used. Results. An increase in nerve number and density was demonstrated in perivascular region around ectopic endometrium as well as in zones of myometrium remodeling in patients with adenomyosis (p <0,001). Nerve growth was associated with degenerative changes in the uterine vessels, lack of a-SMA expression and reduction of estrogen receptors in arteries. These changes were accompanied with stimulation of angiogenesis and increased expression of vascular endothelial growth factor VEGF (p<0,01). The main sources of VEGF were ectopic endometrium epithelium and inflammatory cells in areas of myometrium remodeling. Conclusion. Remodeling of vascular bed and endometrium on the background of dystrophic changes of large vessels and increased VEGF expression could be one of the factors determining nerve growth in uterine adenomyosis.